2013
DOI: 10.1111/dsu.12320
|View full text |Cite
|
Sign up to set email alerts
|

Mohs Micrographic Surgery Concordance Between Mohs Surgeons and Dermatopathologists

Abstract: The high rate of agreement in this study confirms that adequately trained MMS surgeons have sufficient expertise and training for accurate and precise frozen sections interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
9
0
2
Order By: Relevance
“…At the EMC, additional reviews were performed by a pathologist, which increased costs. Other studies show that the rate of slides interpreted in concordance by a MMS surgeon and a pathologist is high (95–100%) . These studies conclude that MMS surgeons are able to review MMS slides as well as pathologists do.…”
Section: Discussionmentioning
confidence: 66%
“…At the EMC, additional reviews were performed by a pathologist, which increased costs. Other studies show that the rate of slides interpreted in concordance by a MMS surgeon and a pathologist is high (95–100%) . These studies conclude that MMS surgeons are able to review MMS slides as well as pathologists do.…”
Section: Discussionmentioning
confidence: 66%
“… 29 Studies carried out in different countries have demonstrated a 99% degree of agreement between Mohs surgeon and dermatopathologist in the evaluation of clear margins. 30 , 31 , 32 , 33 In the present study, the agreement of the aggressiveness of the BCCs was assessed in the preoperative biopsy; the kappa score demonstrated a substantial agreement between the Mohs surgeon and the dermatopathologist. This variation in the classification of subtypes has already been evaluated in other studies, such as that by Genders et al, in which two dermatopathologists evaluated the MMS slides, with substantial agreement, similar to the present study.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies show high interpersonal agreement between Mohs surgeons and pathologists (95–99%) on BCC presence . These studies overestimate the reliability of diagnosis from Mohs slides because they report concordance rates instead of κ values.…”
Section: Discussionmentioning
confidence: 93%
“…1,2 Previous studies show high interpersonal agreement between Mohs surgeons and pathologists (95-99%) on BCC presence. [17][18][19][20][21][22] These studies overestimate the reliability of diagnosis from Mohs slides because they report concordance rates instead of j values. In contrast to these studies, we oversampled difficult Mohs slides, which resulted in an underestimated level of agreement.…”
Section: Discussionmentioning
confidence: 99%